Public finances and long-term growth in Europe - evidence from a panel data analysis - Diego Romero De Ávila; Rolf Strauch (European Central Bank (ECB), 2003)
In Lisbon the European Council proclaimed a European growth strategy. It considers an average economic growth rate of around 3 percent as a realistic prospect for the coming years and assigns public finances an important role in the process of achieving this goal. This paper addresses the question whether we can find empirical evidence for European countries that public finance reform affects trend growth. Focusing on time series patterns, we investigate whether there have been persistent shifts or trends in economic growth and fiscal variables over the last 40 years. In addition, we estimate a distributed lag model, which 1) indicates that government consumption and transfers negatively affect growth rates of GDP per capita over the business cycle, while public investment has a positive impact, and 2) provides robust evidence that distortionary taxation affects growth in the medium-term through its impact on the accumulation of private physical capital.
Keywords: C22; C23; H11; O11; 330; Europe; long-term growth; public finance